Underdiagnosed obstructive sleep apnea detected by respiratory polygraphy in hospitalized patients with heart failure at a tertiary hospital in Lima-Peru - Bazán Lavanda, Eduardo (2025)
Background: Obstructive Sleep Apnea (OSA) is often undiagnosed in heart failure (HF) patients. Early identification using affordable sleep studies could improve patient outcomes in resource-limited clinical settings like Peru. The objective was to determine the frequency of OSA in hospitalized HF patients using respiratory polygraphy (RP) (Sleep Study Type III). Materials and methods: A cross-sectional study was conducted. We included patients >18 years, hospitalized with exacerbated HF, and a STOP-BANG score ≥ 3. Enrolled patients underwent overnight RP using ApneaLink Air™. Data collected included clinical parameters, the Epworth Sleepiness Scale, and echocardiography results. Statistical analysis was carried out using R Studio. Results: Of 46 enrolled patients, 39 underwent successful RP; 84.61% were diagnosed with OSA. Patients exhibited a mean Apnea-Hypopnea Index (AHI) of 14.41 ± 10.08/h with mild (51.28%), moderate (25.64%), and severe (7.69%) cases. Symptoms associated with OSA included a lack of restorative sleep and concentration problems. RP data showed a mean minimum SpO2% of 76.85 ± 9.99% and an Oxygen Desaturation Index (ODI) of 20.01 ± 10.66. Correlation analysis indicated a strong positive correlation between AHI and ODI (r = 0.73, p < 0.001) and a moderate negative correlation between AHI and LVEF (r =-0.64, p = 0.056). Conclusion: This study reveals a high frequency of previously undiagnosed OSA among hospitalized heart failure patients in our institution, indicating the importance of active screening in this high-risk population.